1997
DOI: 10.1172/jci119384
|View full text |Cite
|
Sign up to set email alerts
|

The role of alveolar macrophages in Pneumocystis carinii degradation and clearance from the lung.

Abstract: Although studies indicate that alveolar macrophages participate in host defense against Pneumocystis carinii , their role in organism degradation and clearance from the lung has not yet been established. We, therefore, quantified the uptake and degradation of 35 S-labeled P. carinii by cultured macrophages, demonstrating significant degradation of P. carinii over 6 h. We further evaluated the role of macrophages in elimination of P. carinii from the living host. Rats received either intratracheal PBS, liposoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
150
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 55 publications
4
150
0
3
Order By: Relevance
“…Alveolar macrophages (AMs) are critical components of the pulmonary innate immune response to infectious challenge and likely represent important effector cells in the host response to Pneumocystis (Limper et al, 1997;Steele et al, 2003). Human AMs express surface innate immune receptors such as mannose receptors (Greenberg and Grinstein, 2002) that can mediate Pneumocystis phagocytosis (Ezekowitz et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Alveolar macrophages (AMs) are critical components of the pulmonary innate immune response to infectious challenge and likely represent important effector cells in the host response to Pneumocystis (Limper et al, 1997;Steele et al, 2003). Human AMs express surface innate immune receptors such as mannose receptors (Greenberg and Grinstein, 2002) that can mediate Pneumocystis phagocytosis (Ezekowitz et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely reported that phagocytosis by alveolar macrophages (AMs) is the predominant mechanism of Pneumocystis murina clearance from the lungs (6)(7)(8); however, the mechanisms by which macrophages kill P. murina are not completely understood. It is hypothesized that on phagocytosis, the oxidative burst by macrophages, primarily the generation of hydrogen peroxide and superoxide, has a direct cytotoxic effect on P. murina (9,10).…”
mentioning
confidence: 99%
“…carinii trophozoites were isolated from infected lungs as described previously (8) and then labeled by incubating 4 ϫ 10 7 organisms in 2 ml of Dulbecco's minimum essential medium (DMEM) containing 250 Ci of ProMix reagent (Amersham Biosciences, Piscataway, N.J.) (containing a mixture of [ 35 S]methionine and [ 35 S]cysteine) for 18 h at 37°C with 5% CO 2 as described by Limper et al (21). Unincorporated label was removed from P. carinii by washing the organisms repeatedly in 500 l of DMEM containing 1 mg of bovine serum albumin (BSA) per ml until an insignificant amount of radioactivity was detected in the wash.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of alveolar macrophages is shown by the demonstration that Pneumocystis organisms are not cleared in alveolar macrophage-depleted rats (21). In addition, administration of granulocyte-macrophage colony-stimulating factor, which has been shown to activate alveolar macrophages during Pneumocystis infection (30), decreases the severity of PcP (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation